Rufus Estes: Good Things to Eat As Suggested by Rufus - Jaine, Tom (Petits Propos Culinaires, 2024)
Rufus Estes: Good Things to Eat As Suggested by Rufus: Howling at the Moon Press, Jenks, Oklahoma, 1999: ISBN 0-9654333-1-5:142 pp., b/w photos, p/b, $19.95.